The right of an accused person in a preliminary inquiry in Malaysia / Amiruddin Mohd Akhir - Mohd Akhir, Amiruddin (Faculty of Law, 1987)
The objective of this project is to set forth the various rights of an accused person in Malaysia. now in force at the preliminary inquiry or pre-trial, to stress on the defects, to explain on their effects and operation by reference, where necessary to decided cases and wherever possible, to suggest reform or amendment to the existing law and practice relating thereto. Research for this project paper was conducted at Perpustakaan Tun Abdul Razak, MARA Institute of Technology and the University Malaya Law Library. Lastly, the writer in concluding the paper submitted that the legal position of the accused's rights at a preliminary inquiry stage seems to be far from sufficient for the protection of the accused. It is, however, has not been the writer's intention to provide solutions to problems, but to provoke thought and to provide material from which possible solutions to problem as may he arrived at .